Suppression of Medulloblastoma Lesions by Forced Migration of Preneoplastic Precursor Cells with Intracerebellar Administration of the Chemokine Cxcl3 - Ceccarelli, Manuela; Micheli, Laura; Tirone, Felice (Frontiers in Pharmacology, 2016)
Medulloblastoma (MB), tumor of the cerebellum, remains a leading cause of cancer-related mortality in childhood. We previously showed, in a mouse model of spontaneous MB (Ptch1+/-/Tis21-/-), that a defect of the migration of cerebellar granule neuron precursor cells (GCPs) correlates with an increased frequency of MB. This occurs because GCPs, rather than migrating internally and differentiating, remain longer in the proliferative area at the cerebellar surface, becoming targets of transforming insults. Furthermore, we identified the chemokine Cxcl3 as responsible for the inward migration of GCPs. As it is known that preneoplastic GCPs (pGCPs) can still migrate and differentiate like normal GCPs, thus exiting the neoplastic program, in this study we tested the hypothesis that pGCPs within a MB lesion could be induced by Cxcl3 to migrate and differentiate. We observed that the administration of Cxcl3 for 28 days within the cerebellum of one-month-old Ptch1+/-/Tis21-/- mice, i.e., when MB lesions are already formed, leads to complete disappearance of the lesions. However, a shorter treatment with Cxcl3 (two weeks) was ineffective, suggesting that the suppression of MB lesions is dependent on the duration of Cxcl3 application. We verified that the treatment with Cxcl3 causes a massive migration of pGCPs from the lesion to the internal granular layer (IGL), where they differentiate. Thus, the induction of migration of pGCPs in medulloblastoma lesions may open new ways to treat MB that exploit the plasticity of the pGCPs, forcing their differentiation. It remains to be tested whether this plasticity continues at advanced stages of medulloblastoma. If so, these findings would set a potential use of the chemokine Cxcl3 as therapeutic agent against MB development in human preclinical studies.